Microwave and autoclave usage in human teeth sterilization - MONTEIRO,Rafael Jordão Storino Vaz (2018)
ABSTRACT Objective: evaluate the sterilization of human teeth irradiated by microwaves. Methods: Sixty human third molars are divided into three groups (n = 20): G1 without sterilization (negative control); G2 - autoclaving for 20 minutes 1Kgf/cm2 at 120 ° C (positive control); G3 - sterilization in a microwave vessel containing 200ml of distilled water in a microwave irradiated at 650W for 3 minutes. Results: No culture media of G2 and G3 presented contamination after autoclaving and microwave sterilization. Conclusion: Autoclave sterilization and microwave sterilization were effective decontamination methods under the experimental conditions tested.